2011
DOI: 10.1158/0008-5472.sabcs11-pd09-08
|View full text |Cite
|
Sign up to set email alerts
|

PD09-08: Combined Inhibition of mTORC1 with Temsirolimus and HER2 with Neratinib: A Phase I/II Study in Patients with Metastatic HER2−Amplified or Triple-Negative Breast Cancer.

Abstract: Background: Hyperactivation of the PI3K-AKT-mTOR pathway is a postulated mechanism of resistance to anti-HER2 therapies and has also been described in triple-negative breast tumors. In HER2−amplified (HER2+) laboratory models, inhibition of this pathway induces activation of upstream receptor tyrosine kinases such as HER3. In triple-negative breast cancer (TN), HER1 overexpression has been identified and models show sensitivity to combined HER1 and mTOR inhibition. We hypothesize that dual inhibition of the PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…To date, there have been two reported trials involving temsirolimus, one phase II trial 138 and one phase I 139. Of the 31 patients in the phase II trial, none had an objective response to temsirolimus.…”
Section: Other Therapeutic Targetsmentioning
confidence: 99%
“…To date, there have been two reported trials involving temsirolimus, one phase II trial 138 and one phase I 139. Of the 31 patients in the phase II trial, none had an objective response to temsirolimus.…”
Section: Other Therapeutic Targetsmentioning
confidence: 99%
“…A Phase II trial of erlotinib with chemotherapy is currently underway to assess the pathological clinical response of neoadjuvant chemotherapy plus erlotinib in patients with TNBC (NCT00491816). Figure 3) [59], and neratinib, a substituted quinolone inhibitor (9, Figure 3) [60]. Both compounds are orally bioavailable dual inhibitors of EGFR and human epidermal growth factor receptor 2 (HER2).…”
Section: Egfr Inhibitorsmentioning
confidence: 99%
“…Neratinib is undergoing a Phase I/II trial in combination with the mTOR inhibitor, temsirolimus in patients with metastatic HER2-amplified or TNBC (NCT01111825). The results from a Phase I trial showed the combination was well tolerated with a response rate (RR) of 67% [60].…”
Section: Egfr Inhibitorsmentioning
confidence: 99%
“…In an ongoing phase 1/2 study of neratinib in combination with temsirolimus in patients who previously received trastuzumab therapy, six patients treated at the MTD (8 mg intravenous) were evaluable for response, four achieved partial response, and one had stable disease (ClinialTrials.gov identifier NCT01111825). 82 Phase 2 study results in 117 patients with advanced breast cancer who received no more than two prior trastuzumab regimens and who were randomly assigned to receive neratinib or lapatinib plus capecitabine have been reported. 83 For neratinib and combination therapy, median PFS was 4.5 and 6.8 months (HR 1.3, 95% CI 1.0-1.8, P = 0.091) and median OS was 19.4 and 19.0 months, respectively (P = 0.180; and ORR was 29% and 41%, P = 0.067), indicating that neratinib monotherapy was not as effective as lapatinib plus capecitabine (ClinicalTrials.gov identifier NCT00777101).…”
Section: Investigational Options For Her2 + Therapy-resistant Breast mentioning
confidence: 99%